Saturday
March 25, 2017

Post a New Question

Posted by on .

Please help me solve this equation.

log[2](3)+log[2](x)=log[2](5)+log[2](x-2)

1. Solve equation by setting up algebraically.
2. Use appropriate properties of Logarithm to reduce the number of logarithmic terms to only one.
3. Solve logarithmic equation.

  • calculus - ,

    log[2](3)+log[2](x)=log[2](5)+log[2](x-2)
    =>
    log[2](3*x) = log[2](5*(x-2))
    =>
    3x=5(x-2)
    =>
    5x-3x=5*2
    =>
    2x=10
    =>
    x=5

    Check by putting x into the original equation and see if it balances.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question